Raum und Interieurs in Thomas Manns Erzählwerk - Reidy, Julian (De Gruyter, 2018)
Das 19. Jahrhundert sei „wohnsüchtig
10.1515/9783110589696
Keywords: Hochschulschrift; Mann; Thomas; Roman; Innenarchitektur; Raum; Wohnung